The Role of TikTok Application as A Marketing Media and Sales Increase at PT. Kakha Berdaya Bersama - Bariq, Muhammad; Muthohar, Muchsin (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2023)
Marketing using social media today has increased over time. Social media is a bridge for online sellers and buyers who provide services from anywhere and anytime. The TikTok application has become one of the social media as well as e-commerce applications that have been widely used for the marketing process. Solving problems faced during the internship was done using a qualitative-descriptive approach. It was found that PT. Kakha Berdaya Bersama has not used the rapidly growing Tiktok application as its marketing medium. Hence, it was agreed to adopt the TikTok application as a new marketing medium by carrying out development and trials in marketing. The results show that the TikTok application has a positive and influential role as a marketing medium. Marketing and sales using the TikTok application have been proven to increase sales by 12% and increase sales in 2022–2023, reaching 101%. Thus, using the Tiktok application as a marketing and sales medium is significantly positively correlated with an increase of twofold. Optimization of features in the form of hashtags (#hashtags) can reach more potential customers, and the presence of brand ambassadors can increase customer trust, interest, and intention to buy products that have been marketed.